2010
DOI: 10.1103/physrevb.81.115205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental elucidation of vacancy complexes associated with hydrogen ion-induced splitting of bulk GaN

Abstract: We present a detailed study of the thermal evolution of H ion-induced vacancy related complexes and voids in bulk GaN implanted under ion-cut conditions. By using transmission electron microscopy, we found that the damage band in as-implanted GaN is decorated with a high density of nanobubbles of ϳ1 -2 nm in diameter. Variable energy Doppler broadening spectroscopy showed that this band contains vacancy clusters and voids. In addition to vacancy clusters, the presence of V Ga , V Ga -H 2 , and V Ga V N complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Some evidence of N vacancies with positrons has been found in irradiated (Tuomisto, Ranki et al, 2007) and Mg-doped GaN samples , but further studies are clearly required. Thanks to the abundance of defects generated during growth of GaN or other III-nitrides, irradiation and ion implantation studies are rather scarce (Tuomisto, Pelli et al, 2007;Tuomisto, Ranki et al, 2007;Uedono et al, 2007;Moutanabbir et al, 2010;Mäki, Makkonen et al, 2011). Technologically important alloys such as InGaN and AlGaN have also been studied Chichibu et al, 2011;Uedono et al, 2012).…”
Section: Novel Semiconductors: Iii-n Sic and Znomentioning
confidence: 99%
“…Some evidence of N vacancies with positrons has been found in irradiated (Tuomisto, Ranki et al, 2007) and Mg-doped GaN samples , but further studies are clearly required. Thanks to the abundance of defects generated during growth of GaN or other III-nitrides, irradiation and ion implantation studies are rather scarce (Tuomisto, Pelli et al, 2007;Tuomisto, Ranki et al, 2007;Uedono et al, 2007;Moutanabbir et al, 2010;Mäki, Makkonen et al, 2011). Technologically important alloys such as InGaN and AlGaN have also been studied Chichibu et al, 2011;Uedono et al, 2012).…”
Section: Novel Semiconductors: Iii-n Sic and Znomentioning
confidence: 99%
“…24,25 Subsequent annealing and a combination of the buildup of internal gas pressure in the cavities and the growth of the micro-cavities leads to layer splitting by micro-crack propagation. Moutanabbir et al, (2010a) 26 concluded that thermoevolution of defects in H implanted and annealed freestanding GaN under ion-cut conditions revealed nanobubbles of 1-2 nm in diameter formation around the damage band. These nanobubbles continue to grow and their density and diameter increased during annealing.…”
Section: Resultsmentioning
confidence: 99%
“…The changes in the morphology of hydrogenated defects during annealing proved to be the crucial contribution to the decrease in Si hardness. Moutanabbir et al (2010b) 26 argued that annealing above a critical temperature leads to a relaxation of the internal strain by surface microcracking in H implanted and annealed freestanding GaN under ion-cut conditions. They continued to argue that the intrinsic mechanical properties as well as the nature of the H-induced defects may be critical in determining the implant fluence of H ions needed to cleave GaN.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the anisotropy of the Si lattice and the H agglomeration process [6,7]. Likewise, in III-nitride semiconductors such as polar (0 0 0 1) GaN, H-implantation-induced defects are shown to be passivated by the implanted hydrogen in a definite composition [8,9]. This creates various H-induced defect (HID) complexes such as V N H n and V Ga H n [8].…”
mentioning
confidence: 94%
“…Likewise, in III-nitride semiconductors such as polar (0 0 0 1) GaN, H-implantation-induced defects are shown to be passivated by the implanted hydrogen in a definite composition [8,9]. This creates various H-induced defect (HID) complexes such as V N H n and V Ga H n [8]. These HID complexes become thermodynamically unstable at temperatures (T HID ) of $400°C [8][9][10].…”
mentioning
confidence: 96%